(untitled) (Palíndromo, 2025)
This artistic proposition presents a photographic series composed of 3x4 images from different moments of my life, cut out and overlaid to form a timeless, multigender patchwork face. The series operates as a visual device for autobiographical investigation, in which the image functions as the primary field of meaning production. The photographs articulate questions of identity, body, and social legibility, revealing the artificiality of gender categories, both those fabricated by cisheteronormativity—woman and man—and those re-fabricated by sex-gender dissidences, such as sapatão, bofinho, and sapatransviade. The text that accompanies the work acts as a reflective layer derived from the experience with the images, articulating episodes of social recognition, medical transition, and the everyday negotiations of gender. Grounded in Monique Wittig’s critique, the work proposes identity as an assemblage in constant revision, in which the body is configured simultaneously as archive, site of dispute, and space of self-construction.